Microbial and Chemical Characterization of Natural-Style Green Table Olives from the Gordal, Hojiblanca and Manzanilla Cultivars - José Luis Ruiz-Barba; Antonio Higinio Sánchez; Antonio López-López; Amparo Cortés-Delgado; Alfredo Montaño (Foods, 2023)
Microbial and biochemical changes in the brine during the spontaneous fermentation of Gordal, Hojiblanca and Manzanilla olive cultivars processed according to the natural style were monitored. The microbial composition was assessed through a metagenomic study. Sugars, ethanol, glycerol, organic acids and phenolic compounds were quantified by standard methods. In addition, the volatile profiles, contents of phenolic compounds in the olives and quality parameters of the final products were compared. Fermentation in Gordal brines was conducted by lactic acid bacteria (mainly Lactobacillus and Pediococcus) and yeasts (mainly Candida boidinii, Candida tropicalis and Wickerhamomyces anomalus). In Hojiblanca and Manzanilla brines, halophilic Gram-negative bacteria (e.g., Halomonas, Allidiomarina and Marinobacter) along with yeasts (mainly, Saccharomyces) were responsible for the fermentation. Higher acidity and lower pH values were reached in Gordal brines compared to Hojiblanca and Manzanilla. After 30 days of fermentation, no sugars were detected in Gordal brine, but residual amounts were found in the brines from Hojiblanca (<0.2 g/L glucose) and Manzanilla (2.9 g/L glucose and 0.2 g/L fructose). Lactic acid was the main acid product in Gordal fermentation, whereas citric acid was the predominant organic acid in the Hojiblanca and Manzanilla brines. Manzanilla brine samples showed a greater concentration of phenolic compounds than Hojiblanca and Gordal brines. After a 6-month fermentation, Gordal olives were superior compared to the Hojiblanca and Manzanilla varieties regarding product safety (lower final pH and absence of Enterobacteriaceae), content of volatile compounds (richer aroma), content of bitter phenolics (lower content of oleuropein, which resulted in less perceived bitterness) and color parameters (more yellow and lighter color, indicating a higher visual appraisal). The results of the present study will contribute to a better understanding of each fermentation process and could help to promote natural-style elaborations using the above-mentioned olive cultivars.